Interaction in Digital News Media From Principles to Practice (Springer International Publishing, 2018)
Digital News Media (DNM) are characterized by their efforts to provide consumers with new content interaction experiences, which contrast with the more passive experiences provided by traditional news media. This book directly addresses these interaction experiences, taking the reader from underlying principles to actual practices. To meet this objective, the book undertakes a characterization of interactivity in DNM and explores the boundaries between storytelling and direct data access. It examines information visualization trends present in the media, and practices in non-fiction storytelling in the context of the current wave of VR technology. Moreover, it addresses how UX research and evaluation methods can be applied to inform the design of interactive media. It also analyzes the concept of Newsonomics and it examines the reform of intellectual property law and legislation governing authors' rights. The book concludes by analyzing the scientific production of interaction over the last 10 years, extracting the main conclusions, and highlighting the lessons that can be extracted from the previous chapters.